Multiband Spectropolarimetry of Lunar Maria, Pyroclastics, Fresh Craters, and Swirl Materials - Christian Wöhler; Mirza Arnaut; Megha Bhatt (The Astronomical Journal, 2024)
Imaging polarimetry is a well-known method for examining the small-scale structure of the surface regolith of airless celestial bodies. In this study, we examine (for the first time) the wavelength-dependent polarization behavior of selected lunar areas, including maria, highlands, fresh craters, pyroclastic deposits, and the Reiner Gamma swirl, based on telescopic multiband UBVRI imaging polarimetry at phase angles within the range of the positive polarization branch. The terrain-dependent spectropolarimetric behavior is studied for the first time in this work. For each study area, we conduct a mapping of the relative regolith grain size, an analysis of the exponent of the Umov law, and the wavelength dependence of the degree of linear polarization. Furthermore, we perform area-specific principal component analyses of the degree of linear polarization, followed by unsupervised machine learning (clustering) to segment different terrain types. We find that fresh mare craters and high-titanium pyroclastic deposits have an increased regolith grain size, whereas crater ray material, low-titanium pyroclastic material, and the Reiner Gamma swirl are more finely grained than the average regolith. The degree of linear polarization decreases with increasing wavelength-dependent albedo according to a power law whose exponent is itself positively correlated with the albedo. For a constant albedo and grain size, the degree of linear polarization increases linearly with wavelength. The clustering step yields a library of terrain-dependent prototype spectra of the degree and angle of linear polarization.